Videodistraction to reduce agitation in elderly patients in the emergency department: an open label parallel group randomized controlled trial - Güvec, Enver; Koedel, Uwe; Horster, Sophia; Pedersen, Vera; Völk, Stefanie; Waldow, Michaela; Weber, Florian; Klein, Matthias (European journal of emergency medicine, 2025)
Background and importance - Agitation of elderly patients in the emergency department (ED) often complicates workup and therapy. - Objective - In this study, we investigated if agitation in the ED can be reduced by showing calming video sequences in elderly agitated patients. - Designs - Prospective randomized intervention study. - Settings and participants - ED patients aged ≥65 years were screened for the risk of agitation/delirium using the 4-A’s test (4-AT) test. In case of ≥4 4-AT points, patients were scored using the Richmond Agitation-Sedation Scale (RASS) and the Nursing Delirium Screening Scale (Nu-DESC). They were included in the study if RASS was ≥+2 and Nu-DESC ≥ 4 after informed consent of the legal representative. Patients were then randomized to the intervention or control group. A total of n = 57 patients were included in the study. - Intervention - Patients in the intervention group were exposed to projections of calming video sequences for 60 min. Patients in the control group received standard care. - Outcome measures and analysis - Changes in RASS and Nu-DESC were assessed 30 and 60 min after the intervention was started. - Main results - A total of 57 patients were included in the study, with 30 patients in the intervention group and 27 patients in the control group. Before the intervention, the median (interquartile range) RASS scores were comparable between the intervention group [3 (2-3)] and the control group [3 (2-3)]. After 30 min of exposure to calming video sequences, patients in the intervention group showed significantly lower RASS and Nu-DESC scores compared to the control group [RASS: 1 (0-1) vs. 2 (1.5-3), P < 0.001; Nu-DESC: 3 (2-4) vs. 5 (4-6), P < 0.001]. This difference persisted at 60 min [RASS: 0 (0-1) vs. 2 (1-2.5), P < 0.001; Nu-DESC: 2 (2-3) vs. 5 (4-6), P < 0.001]. Additionally, fewer patients in the intervention group required additional sedating or antipsychotic medication (1/30) compared to the control group (9/27), with this difference being statistically significant (P = 0.004). - Conclusion - In this randomized controlled trial, the use of calming video sequences in elderly patients with agitation in the ED resulted in significant reductions in agitation and the need for additional sedative or antipsychotic medication.